Bullying on Elementary School Students - Devita, Y; Dyna, F (KnE Life Sciences, 2019)
Bullying usually occurs around the school environment such as in the class, toilet, corridor, or after school activities. This research aims to identify bullying behavior on students at schools. The total number of samples were 400 students of State Elementary School determined by using Cluster Sampling Technique. Data collection was done in April – August 2018 randomly in 12 districts in Pekanbaru City. The research results showed the parenting pattern that mostly applied by the kids parents was parental control in the amount of 228 people (57%), the highest number of fathers’ job is informal job in the amount of 238 people (59,5%), the highest number of mothers’ job is being housewives in the amount of 201 people (50,2%), the highest number of violence media is not explored in the amount of 288 people (72%), the highest number of fight is never in the amount of 265 people (66,2%), and the highest verbal abuse is never listening to verbal abuse in the amount of 323 people (80,8%). The highest number of bullying is incurrence of bullying behavior in the amount of 212 people (53,3%), with the highest number of physical bullying in the amount of 211 people (52,8%), the highest number of verbal bullying in the amount of 207 people (51,8%), and mental/psychological bullying in the amount of 249 people (62,3%). The results of this research can be a reference for the schools in preventing the occurrence of bullying behavior on school students. Keywords: bullying, school age kids, elementary school